2022
DOI: 10.1038/s41598-022-19664-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of vinyl-based silica nanoparticles by sol–gel method and their influences on network microstructure and dynamic mechanical properties of nitrile rubber nanocomposites

Abstract: Non-agglomeration and dispersion of silica nanoparticles in polymers and their interfacial interactions to polymer matrix are the most important factors that influence nanocomposites performance. In this work, vinyltriethoxysilane (VTES) as a low VOC emission coupling agent was used for surface modification of silica nanoparticles to prepare better dispersion in nitrile rubber (NBR) and improve its interfacial interactions to silica nanoparticles. The results of X-ray photoelectron spectroscopy, thermogravimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 53 publications
(47 reference statements)
1
29
0
Order By: Relevance
“…The results show that by incorporating pure CeO 2 nanoparticles into the rubber compound, the torque decreased to some extent (see Figure a,b). This should be attributed to the presence of surface hydroxyl groups that prohibit the complete vulcanization of rubber compounds. Figure c shows that even after silanization of nanoparticles at an optimal concentration (i.e., X = 10), the torques decreased compared to pristine rubber. This should be attributed to the lower chance of grafting of silane molecules on the nanoparticle surface due to low OH content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that by incorporating pure CeO 2 nanoparticles into the rubber compound, the torque decreased to some extent (see Figure a,b). This should be attributed to the presence of surface hydroxyl groups that prohibit the complete vulcanization of rubber compounds. Figure c shows that even after silanization of nanoparticles at an optimal concentration (i.e., X = 10), the torques decreased compared to pristine rubber. This should be attributed to the lower chance of grafting of silane molecules on the nanoparticle surface due to low OH content.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrile rubbers (NBRs) have many applications in different industries due to their good resistance to oils, fuels, and organic solvents. However, to use NBR for heavy-duty applications, it needs to be filled with nanofillers to obtain higher chemical/mechanical properties . However, several studies have reported weak dispersion of nanofillers in rubber matrices . The metal-oxide nanoparticles have weak interfacial interactions with the rubber matrix due to their hydrophilic nature that causes their agglomeration and poor dispersion in the rubber matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum torque (M H ) and delta torque (M H –M L ) of composites loaded with silanized HNT were marginally higher than those of their unsilanized counterpart. Consequently, an interaction increased these values following the addition of silanes [ 24 ]. Another explanation would be the dependence of the chemical crosslinks raised from certain silane, as the sulfur atoms, amines, and vinyl groups may influence different crosslinking mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The sol–gel method is a common process for preparing silica–polymer hybrids [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The molecular precursor forms a three-dimensional network within the polymer matrix during the sol–gel reaction [ 78 ].…”
Section: Introductionmentioning
confidence: 99%